The role of echocardiography in the differential diagnosis between training induced myocardial hypertrophy versus cardiomyopathy - Venckunas, T.; Mazutaitiene, B. (Journal of Sports Science & Medicine, 2007)
Increased myocardial mass due to regular high-volume intense exercise training (so-called athlete's heart) is not uncommon. Although directly correlated with the extent of training loads, myocardial hypertrophy is not present exclusively in well-trained or elite athletes. Athlete's heart is considered a physiological phenomenon with no known harmful consequences. However, extreme forms of myocardial hypertrophy due to endurance training resemble a structural heart disease such as hypertrophic cardiomyopathy, a condition associated with substantially increased risk of cardiac event. Endurance sports such as rowing and road cycling, rather than strength/power training, are most commonly associated with left ventricular (LV) wall thickness compatible with hypertrophic cardiomyopathy. The differentiation between physiological and maladaptive cardiac hypertrophy in athletes is undoubtedly important, since untreated cardiac abnormality often possesses a real threat of premature death due to heart failure during intense physical exertion. Luckily, the distinction from pathological hypertrophy is usually straightforward using transthoracic echocardiography, as endurance athletes, in addition to moderately and proportionally thickened LV walls with normal acoustic density, tend to possess increased LV diameter. In more uncertain cases, a detailed evaluation of myocardial function using (tissue) Doppler and contrast echocardiography is effective. When a doubt still remains, knowledge of an athlete's working capacity may be useful in evaluating whether the insidious cardiac pathology is absent. In such cases cardiopulmonary exercise testing typically resolves the dilemma: indices of aerobic capacity are markedly higher in healthy endurance athletes compared to patients. Other characteristics such as a decrease of LV mass due to training cessation are also discussed in the article.